2018
DOI: 10.3233/wor-182796
|View full text |Cite
|
Sign up to set email alerts
|

Differences in posture kinematics between using a tablet, a laptop, and a desktop computer in sitting and in standing

Abstract: BACKGROUND: Alternative methods of accessing the internet and performing computing-related work tasks are becoming common, e.g., using tablets or standing workstations. Few studies examine postural differences while using these alternative methods. OBJECTIVE: To assess neck and upper limb kinematics while using a tablet, laptop and desktop computer (sitting and standing). METHODS: Differences in neck flexion/extension, lateral flexion, rotation; elbow flexion/extension; wrist flexion/extension, radial/ulnar de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…These ergonomic practices may contribute to postures that place greater loads on musculoskeletal structures, leading to MSD. Studies measuring three-dimensional postures show that less ergonomic workstation configurations lead to increased muscle activity 36 and poor postures (e.g., greater head and neck flexion) in individuals with and without MSD 37,38 . Indeed, compared with before the pandemic, during the pandemic fewer respondents reported their most common body posture while working was sitting straight up with their back against a backrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ergonomic practices may contribute to postures that place greater loads on musculoskeletal structures, leading to MSD. Studies measuring three-dimensional postures show that less ergonomic workstation configurations lead to increased muscle activity 36 and poor postures (e.g., greater head and neck flexion) in individuals with and without MSD 37,38 . Indeed, compared with before the pandemic, during the pandemic fewer respondents reported their most common body posture while working was sitting straight up with their back against a backrest.…”
Section: Discussionmentioning
confidence: 99%
“…Studies measuring three-dimensional postures show that less ergonomic workstation configurations lead to increased muscle activity 36 and poor postures (e.g., greater head and neck flexion) in individuals with and without MSD. 37,38 Indeed, compared with before the pandemic, during the pandemic fewer respondents reported their most common body posture while working was sitting straight up with their back against a backrest. Poor postures may contribute to MSD 39,40 and may be reflected in the high numbers of participants reporting MSD in the current study.…”
Section: Changes In Work Environments and Postures During Covid-19 Pa...mentioning
confidence: 99%
“…Working while sitting on sofas or working for long hours on a notebook personal computer (PC) with a relatively small screen is likely to cause/exacerbate musculoskeletal pain. The use of mobile devices including laptop/notebooks or tablets, commonly used by teleworkers, can lead to poor posture, such as neck flexion, compared with the use of desktop PCs [ 22 , 23 ]. Several studies have indicated that sitting with a poor posture can increase the risk of musculoskeletal disorders such as neck or low back pain [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kaya Aytutuldu, et al also found a strong association between symptoms in the upper extremity and those who regularly used computers at work [6]. Yu, et al reported that head and neck issues were associated with poor placement of the screen in mobile computer users (laptop/tablet) [7].…”
Section: Introductionmentioning
confidence: 99%